KORELASI ANTARA KEMAMPUAN MENDENGAR DAN BERBICARA PADA SISWA SEMESTER TIGA PENDIDIKAN BAHASA INGGRIS UNIVERSITAS RIAU - Lispadila, Luchi Putri; Afrianto, Afrianto; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was aimed at finding out the correlation between listening and speaking ability of the third-semester students of English Department Universitas Riau. The researcher implemented a quantitative correlational research design. The number of the samples is 37 selected by using cluster random sampling (CRS). There were two data obtained in this research; students' listening ability and students' speaking ability. The listening TOEFL test was used to collect data of students' listening ability; while students' speaking ability was measured using IELTS speaking test part II. This study found that r-obtained is 0.526 with a significant level 0.001 which means that there is a significant correlation between listening ability and speaking ability. The value of R square shows that the relationship between listening and speaking ability of the students is 27.6%. In other words, it implies that the higher students' listening ability, the higher speaking ability score of the students might get.Keywords: Correlation, Listening ability, Speaking ability.